PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN KURIKULUM MERDEKA BELAJAR - Evy Ramadina (Mozaic : Islam Nusantara, 2021)
The objective of this research is to describe an overview of headmaster in the development of an self regulated learning curriculum. This research is a qualitative research with literature study method. Data analysis used the Miles and Huberman model. Research data obtained from documentation. The findings of the study indicate that: (1) the principal performs the role of supervisor and leader of change in his educational institution, (2) the independent learning curriculum is a student-centered educational program planning, where the education unit has autonomy in curriculum development, (3) the principal Schools have a strategic role in the curriculum development process.